Microalgae as A Bioremediation Agent for Palm Oil Mill Effluent: Production of Biomass and High Added Value Compounds - Putri, Nita Ariestiana; Dewi, Resti Nurmala; Lestari, Rizka; Yuniar, Rizka Ayu; Ma'arif, Luluk Majidah; Erianto, Ricky (Jurnal Rekayasa Kimia & Lingkungan, 2023)
Palm oil mill effluent (POME) is high strength wastewater obtained from palm fruit processing, which contains high chemical oxygen demand (COD), biological oxygen demand (BOD), and other contaminants. The pollutant load in POME can serve as a source of nutrients for microalgae growth. As a result, the goal of this work was to utilize Spirulina sp. and Nannochloropsis oculata to reduce the nutritional content of POME while producing biomass rich in high-value chemicals. The cultivation was conducted in a batch reactor using various POME fractions (0-20%) under 5,000 lux light intensity and continuous aeration at a temperature of 22-28C and a salinity of 30 ppt for 14 consecutive-days. The results demonstrate that Spirulina sp. produced the most biomass at 15% POME, accounting for 4.670.95 g/L with 0.570.11 1/day of growth rate and 3.33% of COD reduction efficiency. Meanwhile, Nannochloropsis oculata thrived in 20% POME, producing 4.430.36 g/L biomass, 1.180.31 1/day growth rate, and 14.43% COD reduction efficiency. In the proximate analysis. Spirulina sp. and Nannochlorpsis oculata provided 0.87%; 1.11% lipid and 1.03%; 0.86% protein, respectively.